PLAYING TO LEARN HOW LIVE TOGEDER (Fiep Bulletin - online, 2011)
Field research using the method of experimental procedure, focused on the game interface to control the aggressiveness of children. Aimed to diagnose and assess possible changes in social behavior of children aged 4 to 6 years of EMEI CEU Park Paths. Based on studies of authors who cite the games as an important forum for expression, social interaction, thinking and communication and foster self-esteem of children and internalizing behaviors of the social group in which it operates. We evaluated 15 students (9 boys and 6 girls) participated in the Sports Program workshops since February 2008, the study period was from August to December (21 lessons). A questionnaire was applied to closed two teachers from the classroom and used the logbook the teacher to observe the behavior in the classroom before and after the experiment, to record the number of fights. At the end of the experiment showed a decrease in the number of fights: the first 43 months and 1 in the last month of school. Thus, it appears that the games were important for the social integration of students, which became a factor in the transformation of social behavior and aggressive behavior of students.
Keywords: Aggressive Children; Games; Physical Education Children